Comparative Transcriptome Analysis of Litopenaeus vannamei Reveals That Triosephosphate Isomerase-Like Genes Play an Important Role During Decapod Iridescent Virus 1 Infection - Liao, Xuzheng; Wang, Chenggui; Wang, Bo; Qin, Haipeng; Hu, Shikang; Wang, Ping; Sun, Chengbo; Zhang, Shuang (Frontiers in Immunology, 2020)
Decapod iridescent virus 1 (DIV1) results in severe economic losses in shrimp aquaculture. However, little is known about the physiological effect of the DIV1 infection on the host. In this study, we found that the lethal concentration 50 (LC50) of DIV1 infected Litopenaeus vannamei after 48, 72, 96 and 156 hours were 4.86 × 106, 5.07 × 105, 2.13 × 105, and 2.38 × 104 copies/μg DNA, respectively. In order to investigate the mechanisms the DIV1 infection, comparative transcriptome analysis of hemocytes from L. vannamei infected, or not, with DIV1 were conducted. A total of 168,854 unigenes were assembled, with an average length of 601 bp. Based on homology searches, kyoto encyclopedia of genes and genomes (KEGG), gene ontology (GO), and cluster of orthologous groups of proteins (KOG) analysis, 62,270 (36.88%) unigenes were annotated. Among them, 1,112 differentially expressed genes (DEGs) were identified, of which 889 genes were up-regulated and 223 genes were down-regulated after DIV1 infection. These genes were mainly annotated to the major metabolic processes such as fructose and mannose metabolism, carbon metabolism, and inositol phosphate metabolism. Among these metabolic pathways, the triosephosphate isomerase (TPI) family was the most eye-catching DEG as it participates in several metabolic processes. Three types of TPI, LvTPI-like, LvTPI-Blike, and LvTPI-Blike1 were obtained for gene silencing by RNA interference (RNAi). The results showed that LvTPI-like and LvTPI-Blike1 silencing caused a high mortality rate among L. vannamei. However, LvTPI-like and LvTPI-Blike silencing reduced DIV1 replication in DIV1 infected L. vannamei. Therefore, TPI-like genes facilitate the replication of DIV1 in L. vannamei, which provides valuable insight into the infection mechanism of DIV1 in shrimp and is may aid in preventing viral diseases in shrimp culture.